(untitled) (Patan Pragya, 2021)
Migration refers to the process of movement from one place to another, such as crossing intra or international geographical boundaries. Sociological studies of migration are diverse. The motive for migration includes political, economic, social, and environmental cause. It is a known fact that Nepali migrants are scattered around the world and many of them are in Gulf country, followed by America and Japan. This micro level study to Dakshinkali Municipality Kathmandu District. The main objectives of this study are to study the causes of migration and its socio-economic impact of the foreign employment in the study area. The total of 71 respondents was surveyed during household questionnaire survey and altogether 6 key informants were interviewed. The trend of abroad migration for foreign employment and higher education has been increasing. Among the total 71 respondents, male migrants are maximum than the female migrants with the age group of 24-29 and 30-34. The majority of people were dependent on agriculture. Despite being farmer, most of them go to the abroad for foreign employment to maintain their living standards. Remittance was mostly used for education, pay debt and other daily accommodations and only few of them invest in land and small business. High rate of wage was the main push and pull factor. In recent years, the migration has been increasing due to increased unemployment and political conflict